Penerapan metode pembelajaran daring dalam mata pelajaran bahasa Indonesia di SDN 1 Guntung Manggis - Ristiani Ristiani (Persatuan Guru Republik Indonesia Kota Banjarbaru, 2022)
This research is motivated by the low learning outcomes of Indonesian students in class III SDN 1 Guntung Manggis which can be seen from the daily test scores of students who have incomplete criteria of 60%, while viriteria are complete 40%. Low learning outcomes are caused because current learning uses the WhatsApp application, so there are some students who do not have cellphones and some of those students are left behind with the learning, some are not very understanding and lack in understanding the material sent by educators via WhatsApp. For this reason, researchers apply online learning methods in Indonesian subjects. The learning method I here uses the WhatsApp grub application, the subjects in this study are class III students with a total of 20 students. Data collection techniques used are observation, interviews and documentation. The results showed good results with the consistency of educators in motivating students and parents of students as learning companions for students in carrying out activities in WhatsApp group such as posting the material to be studied, providing explanations about the material to giving the tasks that were collected.